Evidence mapping of traditional Chinese medicine in diabetic peripheral neuropathy treatment - Fu, Yujie; Wang, Yiming; Li, Zhenghong; Huang, Ke; Gao, Yating; Xu, Shanqiong; Li, Qingna; Liu, Xingfang; Zhang, Guangde (Frontiers in Pharmacology, 2024)
Objective: Diabetic peripheral neuropathy (DPN) stands as a crucial complication of diabetes, significantly affecting patients' quality of life. This study aims to elucidate the evidence distribution from clinical randomized controlled trials (RCTs) on DPN treatment with traditional Chinese medicine (TCM) through evidence mapping.Methods: A comprehensive search was conducted from January 2017 to October 2022 in databases such as Wanfang(China Online Journals), CNKI ( China National Knowledge Infrastructure), VIP(China Science and Technology Journal Database), SinoMed(Chinese Biomedical Literature Database), PubMed, Web of Science, and Cochrane Library. Literature related to the treatment of DPN with TCM was selected. From the 1,229 RCTs identified over the past six years, relevant data were extracted. The evidence mapping approach was utilized, and trends in publications, study scales, intervention types, and evaluation indicators were analyzed using descriptive text combined with tables and bubble charts.Research on the treatment of DPN with TCM is extensive. The publication trend remains relatively stable with predominantly smaller sample sizes. The main treatments encompass oral Chinese medicine and traditional external treatments. The most common evaluation indicators are neurophysiological, efficiency rate, symptom signs, neuropathy scores, and traditional Chinese symptoms, with less focus on psychological status and the anklebrachial index(ABI).Shedding light on contemporary research, this study explores the current RCTs evaluating TCM's efficacy in treating DPN. The findings not only highlight the potential role of TCM in addressing diabetic complications but also underscore areas that could benefit from refined research approaches, expanded intervention methods, and broader assessment criteria. Our observations aim to inform and inspire future research directions and clinical practices concerning TCM's role in managing diabetes-associated complications.